A predictive survival model for patients with head and neck squamous cell carcinoma treated with immune check point inhibitors. (November 2020) - Bonomi, M.; Bhateja, P.; Issa, M.; Klamer, B.; Pan, X.; Blakaj, A.; Karivedu, V.; Mousa, L.; Mitchell, D.; Gamez, M; Kang, S.; Seim, Nolan B.; et al.
Highlights: The minority of patients with head and neck squamous cell carcinoma (HNSCC) will benefit from immune check point inhibitors (ICI). This is a single institutional retrospective review on 121 unresectable or metastatic HNSCC patients treated with ICIs. We predicted that inflammatory markers available through routine blood work, in addition to clinical characteristics may divide patients into groups more or less likely to benefit from these agents. We developed and internally validated a nomogram to predict OS at 1, 2 years and median survival. Abstract: Background: ICIs have expanded treatment options for HNSCC. A minority of the patients respond to these expensive treatments. Patients and methods: This is a single institutional retrospective review on 121 unresectable or metastatic HNSCC patients treated with ICIs. We predicted that inflammatory markers available through routine blood work, in addition to clinical characteristics may divide patients into groups more or less likely to respond to these agents. Here we develop and internally validate our nomogram to predict survival in patients treated with ICIs.